S127 Influenza A and Poly(I:C) Induce α Vβ6-Integrin-Mediated TGFβ Activity in Human Epithelial Cells Via Stimulation of TLR3. (19th November 2012) - Jolly, L; Stavrou, A; Violette, S; Weinreb, P; Hussell, T; Jenkins, G
Abstract : People with chronic lung disease are more susceptible to influenza infection which may lead to exacerbation of pre-existing conditions such as fibrosis. Transforming growth factor-β (TGFβ) is a profibrotic cytokine, but its role during influenza infection remains unclear. Toll-like-receptor 3 is located on the endosomal membrane and binds dsRNA, an intermediate product from replicating ssRNAviruses such as influenza. TLR3 activation has been shown to increase RhoA activity, and we have previously shown that RhoA is a key intermediary inactivation of TGFβ by the αVβ6-integrin. Therefore, we hypothesised that influenza infection could stimulate TLR3 leading to activation of latent TGFβ via this integrin in epithelial cells. Immortalised human bronchial epithelial cells (iHBECs) were used in all experiments. To determine whether influenza virus (A/PR/8/34 H1N1), or poly (I:C) (20µg/ml) were able to activate TGFβ the following TGFβ activation assays were used; detection of phospho-smad2/3 in nuclear extracts of cell lysates by ELISA; analysis of TGFβ activity in cells transiently transfected with a TGFβ-sensitive reporterconstruct; and a co-culture of iHBECS with a TGFβ reporter cell line (TMLCs). To confirm the involvement of TLR3, cells were dual transfected with a TGFβ-sensitive reporter and a dominant negative TLR3 construct designed to prevent TLR3 signalling. The role of the RhoA-ROCK pathway, and αVβ6-integrin were investigated using the ROCK inhibitor H1152, and the αVβ6-integrin blocking antibody 6.3G9, respectively. H1N1 infection and poly(I:C) caused an increase in luciferase in iHBECs transiently transfected with a TGFβ reporter construct. Similarly, both H1N1 and poly(I:C) caused an increase in nuclear phospho-smad2/3 which could be blocked by 6.3G9 peaking at 4h. Both agents caused an increase in TGFβ as measured by a co-culture assay and this could be blocked by H1152 and 6.3G9 suggesting the involvement of ROCK, αVβ6-integrin and the requirement for cell-to-cell contact. Finally, arole for TLR3 in this process was confirmed in cells transfected with a dnTLR3 construct which lost the ability to activate TGFβ in response to poly(I:C) orH1N1. In conclusion, these data show that both influenza A and poly (I:C) lead to increased TGFβ activity in iHBECs. This supports the hypothesis that influenza A infection activates TGFβ via TLR3 and the αVβ6 integrin. These data suggest anovel mechanism by which influenza infection of epithelial cells may promoteairway and lung fibrosis.